Cloud-Assisted Smart Camera Networks for Energy-Efficient 3D Video Streaming. - Guan, Zhangyu; Melodia, Tommaso (Computer (00189162), 2014)
Despite current obstacles, smart camera networks that offload computationally intensive tasks to remote servers could allow energy-efficient 3D and multiview video encoding and delivery yet still ensure high-quality multiple-device video streaming.